2009
DOI: 10.1109/tnsre.2009.2023293
|View full text |Cite
|
Sign up to set email alerts
|

HermesC: Low-Power Wireless Neural Recording System for Freely Moving Primates

Abstract: Abstract-Neural prosthetic systems have the potential to restore lost functionality to amputees or patients suffering from neurological injury or disease. Current systems have primarily been designed for immobile patients, such as tetraplegics functioning in a rather static, carefully tailored environment. However, an active patient such as amputee in a normal dynamic, everyday environment may be quite different in terms of the neural control of movement. In order to study motor control in a more unconstrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 37 publications
0
95
0
1
Order By: Relevance
“…Only in such setups could accurate measurements of behavioral kinematics and neurophysiological activity be taken. However, with the continued evolution of wirelessly transmitting neural recording amplifiers and computer vision technology, preliminary research with unconstrained animal models may be possible [12], [13], [14], [15]. In this study we aim to show that basic motor systems neuroscientific findings of neurally tuned behavior are consistent in unconstrained behavior in one monkey.…”
Section: Introductionmentioning
confidence: 94%
“…Only in such setups could accurate measurements of behavioral kinematics and neurophysiological activity be taken. However, with the continued evolution of wirelessly transmitting neural recording amplifiers and computer vision technology, preliminary research with unconstrained animal models may be possible [12], [13], [14], [15]. In this study we aim to show that basic motor systems neuroscientific findings of neurally tuned behavior are consistent in unconstrained behavior in one monkey.…”
Section: Introductionmentioning
confidence: 94%
“…The use of mobility of network components is considered to be a prospective balancing method. In various studies [3], [13], authors have shown that the use of mobility is good for increasing the autonomous actions of a sensor network. THE WIRELESS SENSOR NETWORK The primary task of the network reconfiguration method is to increase the time interval of the network topology change.…”
Section: Related Researchmentioning
confidence: 99%
“…The ipsilateral arm is also often restrained since motor cortical activity is also related to ipsilateral arm movements (e.g., [10]) However the ipsilateral arm's EMG activity is seldom if ever measured. [32][33][34][35][36] This model has also been employed by Nicolelis, Carmena, and colleagues [12,13] as well as by Andersen, Shenoy, and colleagues, albeit measuring EMG in separate experiments to assure no EMG modulation during an "instructed-delay" period [14,15]. This monkey model "looks like a paralyzed patient," which may be beneficial to BMI research insofar as there are no arm movements or muscle contractions that would lead to sensory signals.…”
Section: A Arm Restrained No Emg Modulationmentioning
confidence: 99%
“…It is now possible to build miniature head-mounted systems to record from multi-electrode arrays, transmit these data wirelessly to a nearby receiver, and use modern computer vision and markerless motion tracking techniques for high-precision behavioral measurement [32][33][34]. In combination, this enables monkeys to move freely and perform a variety of naturalistic tasks while studying how populations of neurons control movement.…”
Section: F Freely Movingmentioning
confidence: 99%